Leveraging TikTok for ELT : A Systematic Review - Sulistianah Sulistianah; Siti Kurniasih; Nafan Tarihoran (Lembaga Pengembangan Kinerja Dosen, 2025)
TikTok, as a social media platform, is increasingly gaining attention in English language teaching (ELT) due to its potential to enhance speaking and listening skills through interactive learning experiences. However, its effectiveness in formal education is still debated due to challenges pedagogical. This study aims to synthesize evidence related to the role of TikTok in English Language Teaching (ELT), specifically its impact on students' speaking, listening, and engagement learning. This study employs a systematic review method based on the PRISMA guidelines, with data search using the keywords “Digital Learning; English Language Teaching (ELT); Learner Engagement; Social Media; TikTok” in five academic databases, namely Scopus (n = 30), Mendeley (n = 25), Publish or Perish (n = 40), Google Scholar (n = 50), as well as additional sources from ResearchGate (n = 4), Academia.edu (n = 1), and institutional repositories (n = 3). Of the 153 studies found, 48 were thoroughly reviewed, and 20 final studies were analyzed. The results show that TikTok can improve students’ pronunciation exercises, listening comprehension, and learning motivation. However, challenges such as content validity, curriculum integration, and potential distractions remain concerns. In conclusion, TikTok has the potential to serve as an additional learning tool in ELT, increasing engagement and language acquisition; however, a structured pedagogical strategy is necessary to maximize its benefits and address existing challenges. More research is needed to identify best practices in integrating TikTok into formal education.